2005
DOI: 10.1182/blood-2004-10-3939
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-catalyzed activation of factor VIII with His substituted for Arg372 at the P1 site

Abstract: Thrombin-catalyzed proteolysis at Arg372 of factor VIII is essential for procofactor activation. However, hemophilia A patients with the missense mutation Arg372 to His possess a mild to moderate phenotype yet show no detectable cleavage at this bond. To evaluate this discrepancy, we prepared and stably expressed a recombinant, B-domainless factor VIII mutant (R372H) that possessed approximately 1% the specific activity of wild type. Cleavage at R372H by thrombin occurred with an approximately 80-fold decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
0
29
1
1
Order By: Relevance
“…The cleavage rate for thrombin at this site was reduced ϳ340-fold for the R1689H variant compared with wild type (Table 1). This value reflects a greater reduction in cleavage rate than the ϳ80-fold reduction that was observed in a prior study when His replaced Arg at the 372 site (25). However, this result is consistent with accommodation of His in the specificity binding pocket of the enzyme, allowing for scissile bond cleavage.…”
Section: Characterization Of Recombinant Factor VIII Protein-contrasting
confidence: 39%
See 1 more Smart Citation
“…The cleavage rate for thrombin at this site was reduced ϳ340-fold for the R1689H variant compared with wild type (Table 1). This value reflects a greater reduction in cleavage rate than the ϳ80-fold reduction that was observed in a prior study when His replaced Arg at the 372 site (25). However, this result is consistent with accommodation of His in the specificity binding pocket of the enzyme, allowing for scissile bond cleavage.…”
Section: Characterization Of Recombinant Factor VIII Protein-contrasting
confidence: 39%
“…To evaluate whether cleavage at Arg-1689 contributes to the thrombin-catalyzed activation of factor VIII and in particular the slow step of cleaving Arg-372, we prepared and stably expressed two recombinant factor VIII mutants, R1689H and R1689Q. Selection of these mutations was based on a previous study evaluating the hemophilia A missense mutation R372H (25). That study demonstrated an ϳ80-fold reduction in the rate of thrombin cleavage at His-372 as compared with Arg-372 in wild-type protein.…”
Section: Characterization Of Recombinant Factor VIII Protein-mentioning
confidence: 99%
“…Samples were subjected to SDS-PAGE using 8% polyacrylamide gels and Western blotting was performed as described previously (22). Blotting used the 58.12 (anti-A1) monoclonal antibody and binding was detected with a goat anti-mouse alkaline phosphatase-linked antibody (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The specific activity of R740H was 50% that of wild-type factor VIII and would yield a normal phenotype, while a specific activity of ϳ20% for the R740Q mutant would yield a mild hemophilia A phenotype. A recent study showed that replacement of Arg 372 with His yielded a factor VIII variant possessing a severe hemophilia A phenotype (1% wild type) and showed an ϳ80-fold reduced rate for thrombin catalyzed cleavage at His 372 (24). While the His 740 mutation resulted in a similar fold reduction in the rate of thrombin cleavage at this site as well as Arg 372 , as judged by A2 subunit generation data, these impairments were not reflected in the specific activity values.…”
mentioning
confidence: 96%
“…To evaluate thrombin cleavage at Arg 740 , two recombinant factor VIII mutants, R740H and R740Q were prepared and stably expressed. These residues were selected based upon a prior study evaluating cleavage at the Arg 372 site (24). In that study, the thrombin-catalyzed cleavage rate at His 372 site was reduced ϳ80-fold relative to Arg at this position, whereas no detectable cleavage was observed for the P1 Gln 372 mutation.…”
Section: Characterization Of Recombinantmentioning
confidence: 99%